Toward a Conceptualization of Mixed Methods Phenomenological Research. (January 2015) - Mayoh, Joanne; Onwuegbuzie, Anthony J.
Increasingly, researchers are recognizing the benefits of expanding research designs that are rooted in one tradition (i.e., monomethod design) into a design that incorporates or interfaces with the other tradition. The flexibility of phenomenologically driven methods provides one such example. Indeed, phenomenological research methods work extremely well as a component of mixed methods research approaches. However, to date, a mixed methods version of phenomenological research has not been formally conceptualized. Thus, the purpose of this article is twofold. First, we provide a philosophical justification for using what we call mixed methods phenomenological research (MMPR). Second, we provide examples of MMPR in practice to underline a number of potential models for MMPR that can practically be used in future research.